PENGGUNAAN INSULIN PADA PASIEN DIABETES MELITUS TIPE 2 PESERTA JKN DI INSTALASI FARMASI RAWAT JALAN RUMAH SAKIT ST. ELISABETH SEMARANG - Fef Rukminingsih; Valentina Catur Nova (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2021)
Diabetes mellitus (DM) type 2 is a chronic and progressive clinical syndrome, characterized by polyuria, polydipsi and polyphagy accompanied by increased blood glucose or hyperglycemia. Management of type 2 diabetes mellitus in patients with HbA1C values > 9% is by administering insulin or a combination of insulin with oral hypoglycemic agents. This study aims to determine the suitability of the type and dose of insulin in type 2 DM patients in the Outpatient Pharmacy Installation of St. Elisabeth Hospital Semarang. This research is a descriptive observational study using retrospective data. The data were obtained from the medical records of Universal Health Coverage participant patients with type 2 diabetes mellitus in the Outpatient Pharmacy Installation of St. Elisabeth Hospital Semarang, who only received insulin therapy in January 2020, is 26-65 years old, and has examination results for fasting blood glucose, post prandial blood glucose and HbA1C (examination results for the last 6 months). The results showed that 57 patients consisted of 29 (50.88%) male patients and 28 (49.12%) female patients. A total of 47 (82.46%) patients were more than 45 years old. A total of 38 patients (66.67%) received combination insulin and all patients had HbA1C values> 9%. The suitability of using insulin based on the type of insulin was 68.42% and most of the patients (80.70%) received inappropriate insulin doses.